A legal study on the viability of enforcing an ownership restrictions in community pharmacies in Malaysia / Dayang Radjwili Hafizah Abang Othman - Abang Othman, Dayang Radjwili Hafizah (2017)
Currently, the law which regulates the ownership restriction in the community pharmacies in Malaysia is not sufficient enough as compared to Australia. Ownership issue is important in ensuring the owner and the licensed registered pharmacists comply with the requirement stipulated under the pharmacy laws. There are several consequences that derived from uncontrolled pharmacy ownership in Malaysia. This includes an increased in the number of corporate chain pharmacy compared to the independent pharmacies which provide more to business-oriented pharmacy services rather than patient-oriented services. The main statute, namely, the Registration of Pharmacists Act 1951 and the related guideline, namely, the Community Pharmacy Benchmarking Guideline 2011 are briefly discussed in this research and are then compared to the Victoria state. In order to gain more details of this issue, a combination of doctrinal and empirical research approach was adapted and semi-structured interview with respondent from the Pharmaceutical Enforcement Department of Selangor. There are several weaknesses and challenges that have been found in the existing laws in restricting the ownership of community pharmacies in Malaysia. Therefore, this research aims to propose some amendments to the Registration of Pharmacists Act 1951 and the Community Pharmacy Benchmarking Guideline 2011 in order for the rule of ownership restriction to be successfully implemented in Malaysia.